New and promising anti-bacterials: Can this promise be sustained? - Sai Saran; Namrata S Rao; Afzal Azim (Wolters Kluwer Medknow Publications, 2020)
The World Health Organization (WHO) announced antimicrobial resistance (AMR) as a major threat to public health which requires that new antimicrobials need to be developed faster than ever before. The rapid development of resistance has rendered many promising antibacterials useless in treating critically ill patients. This article discusses new antibacterials, which got Food and Drug Administration (FDA) approval in the last few years, along with their key pharmacokinetic and pharmacodynamic (PK/PD) advantages, added antimicrobial spectrum, indications, strengths and weaknesses of these drugs from an intensivist point of view. A brief mention has been made on antimicrobial peptides (AMPs), bacteriophages and nanoparticles, which are likely to dominate the future of antibacterials. Finally, it must be understood that the battle against AMR can only be won by a combination of innovative therapies, good infection control practices, strong antibiotic stewardship in the hands of informed healthcare workers.